1982
DOI: 10.1007/bf01965109
|View full text |Cite
|
Sign up to set email alerts
|

Histamine release and hypotensive reactions in dogs by solubilizing agents and fatty acids: Analysis of various components in cremophor El and development of a compound with reduced toxicity

Abstract: Anaphylactoid reactions in man following administration of drugs solubilized with cremophor El (polyethylenglycolglycerol riconoleate) are a considerable clinical problem. Since these reactions occur in dogs on first exposure and in pigs on second exposure, the 'dog model' was used in this communication to analyse components and chemical modifications of cremophor El and its components for their clinical effects, their hypotensive actions and their histamine-releasing capacity. Two series of experiments in 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…However, this communication illustrates by one intensely studied example with one clinically used histamine releaser (experiments in animals and human subjects for more than /0 years [29-32, 34, 39, 40, 44, 54] that the classical symptoms of anaphylaxis are rare in histamine-release responses in general and only more common ("classical") in grade III reactions. Increasing experience, however, in animals [6,25,42,49,50,60] and in man [61] is forming the suggestion that even this may not be true: Clinical pictures of severe heart attack or arrhythmias may be caused by histaminerelease responses which clearly have to be classified as grade III reactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, this communication illustrates by one intensely studied example with one clinically used histamine releaser (experiments in animals and human subjects for more than /0 years [29-32, 34, 39, 40, 44, 54] that the classical symptoms of anaphylaxis are rare in histamine-release responses in general and only more common ("classical") in grade III reactions. Increasing experience, however, in animals [6,25,42,49,50,60] and in man [61] is forming the suggestion that even this may not be true: Clinical pictures of severe heart attack or arrhythmias may be caused by histaminerelease responses which clearly have to be classified as grade III reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the hydrophobic components (composed of 80 % derivatives of ricinoleic acid, 5 % derivatives of oleic acid), only the derivatives of oleic acid released histamine [11]. Further experimentation indicated that the derivatives of 12-hydroxystearic acid were the least dangerous in this test system [13]. In the first part of the study here presented, cremophor E1 and six derivatives of 12-hydroxystearic acid were compared using two models : the anaesthetized dog and isolated mast cells.…”
Section: Discussionmentioning
confidence: 92%
“…There has been much work published on the histamine releasing ability of cremophor and its derivatives using in vivo models [11][12][13]. Cremophor El, produced by the oxethylation of castor oil at elevated temperatures in an alkaline medium, is a mixture of hydrophilic and hydrophobic components [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, not widely known that cyclosporin A is dissolved using cremophor El as a solubilizer. This mixture of fatty acids and its chemically modified derivatives (LORENZ et al 1982b) was demonstrated in a whole series of articles as a histamine releaser (LORENZ et al 1971a(LORENZ et al , 1977b(LORENZ et al , 1981a(LORENZ et al , 1982b and as a potentiator of histamine release responses (ENNIS and LORENZ 1985a. This may explain unexpected cardiovascular reactions and very high plasma histamine levels at certain times after transplantation (LORENZ and DOENICKE 1985a) Finally, histamine is involved in wound healing.…”
mentioning
confidence: 91%